1998
DOI: 10.1111/1469-7610.00350
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Abortion and Parental Notification: Evidence for the Importance of Family Functioning on the Perceived Quality of Parental Involvement in U.S. Families

Abstract: This study was an investigation of the relationship between family variables and the perceived quality of parental involvement following parental notification of an adolescent's decision to have an abortion. Demographics, family religiosity, and family functioning variables were examined. Pregnant adolescent clients from seven abortion clinics in three states completed a survey assessing their perception of the quality of parental involvement and the family variables. Only family functioning variables were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In a study with a somewhat different focus, Mary S. Griffen-Carlson and Paula J. Schwanenflugel examined the factors that might be useful predictors of the quality of parental involvement for those teens who do disclose. 431 They concluded that the most important variable was family functioning, with "adaptability" being the most significant attribute.…”
mentioning
confidence: 99%
“…In a study with a somewhat different focus, Mary S. Griffen-Carlson and Paula J. Schwanenflugel examined the factors that might be useful predictors of the quality of parental involvement for those teens who do disclose. 431 They concluded that the most important variable was family functioning, with "adaptability" being the most significant attribute.…”
mentioning
confidence: 99%